Epigenetic lessons from transgenic plants In: Floricultural, ornamental and plant biotechnology: advances and topical issues - Ingelbrecht, I.L.; Mirkov, T.E.; Dixon, Alfred G.O.; Menkir, A. (2006)
Transgenic plant studies have lead to the breakthrough discovery of RNA silencing as a conserved mechanism for gene regulation across kingdoms. Recent molecular genetic studies have revealed a major role for RNA silencing in the formation of silent chromatin, characterized by histone modifications and dense DNA methylation. These epigenetic marks ensure stable, yet potentially reversible, transmission of the silent state of genetic elements such as transgenes and transposable elements through multiple cell divisions, and in some cases, through successive generations. It is now recognized that epigenetic control mechanisms play a fundamental role in preserving the integrity of the genome against invasive parasitic nucleic acid elements such as viruses and transposons. It is also becoming clear that epigenetic processes are of major evolutionary significance in plants by providing plasticity to the genome to adjust to environmental changes and by stabilizing the genome after polyploidization events. RNA silencing has become a powerful research tool to elucidate gene function in reverse genetics studies and has been applied in the production of virus resistant crops. An enhanced understanding of epigenetic processes is therefore not only of academic interest but will also provide new tools and techniques for plant scientists involved in conventional and biotechnology-based horticultural and agricultural crop improvement.